First report of Lihan Tick virus (Phlebovirus, Phenuiviridae) in ticks, Colombia (2020)
Background: Tick-borne phenuivirus (TBPVs) comprise human and animal viruses that can cause a variety of clinical syndromes ranging from self-limiting febrile illness to fatal haemorrhagic fevers. Objective: Detect Phlebovirus (Family Phenuiviridae) in ticks collected from domestic animals in Córdoba, Colombia. Methods: We collected 2365 ticks from domestic animals in three municipalities of the Department of Cordoba, Colombia in 2016. Ticks were identified and pooled by species for RNA extraction. A nested real-time PCR with specific primers for Phlebovirus and a specific probe for Heartland virus (HRTV) formerly a Phlebovirus, now a Banyangvirus were performed. Also, a conventional nested PCR, with the same specific primers was used to detect other Phleboviruses, with positive reactions indicated by an amplified cDNA fragment of approximately 244 bp determined by gel electrophoresis. These bands were gel-purified and sequenced by the Sanger method. Results: Using real-time RT-PCR, no positive results for HRTV were found. However, using conventional nested PCR 2.2% (5/229 pools) yielded a product of 244 bp. One positive sample was detected in a pool of Dermacentor nitens ticks collected from a horse, and the four remaining positive pools were from Rhipicephalus microplus collected from cattle. The five positive nucleotide sequences had identities of 93 to 96% compared to a section of the Lsegment of Lihan Tick virus, a Phlebovirus originally detected in R. microplus ticks in China. The strongest identity (96–99%) was with Lihan Tick virus detected in R. microplus ticks from Brazil. Conclusions: This is the first report of viral detection in ticks in Colombia. We detected a Colombian strain of Lihan Tick virus. We recommend expanding the sampling area and carrying out more eco-epidemiological studies related to epidemiological surveillance of viruses on ticks in Colombia